Mapeamento de experiências existentes nas universidades federais no combate à violência de gênero e contra as mulheres : subsídios para a construção do Observatório de Gênero Mulheres e Violência na UFSCar - Capovilla, Silmara Helena (Universidade Federal de São Carlos, 2016)
The research aims to raise some innovative actions found in Brazilian federal universities that have as a proposal the fight against gender violence and against women. The idea is that the study contributes to the creation of administrative and pedagogical practices that allow the constitution of projects and alternative solutions for the management of conflicts of gender relations within the universities themselves. For the survey of these actions we opted for an exploratory, bibliographical and documentary qualitative research that made use of the content analysis. From the material analyzed, the categories were defined: consolidated successful experiences and recent successful experiences developed by these universities in relation to the fight against gender violence and against women. As a result, the research demonstrates that there is a need for collection, organization, treatment and continuous dissemination of information generated by the IFES. The proposal of intervention of this research is therefore the conception of a Gender, Women and Violence Observatory for the Extension Project ACIEPE / Women in the Public Administration of the Federal University of São Carlos-UFSCar seeking partnerships with SAADE, NIASE, LAPREV, Nucleus of studies YOU WANT that are located in UFSCar, as well as to promote rapprochement with the community of São Carlos. The objective of the creation of the Observatory is to promote the identification of policies to combat violence, the mapping of host networks, the monitoring of indicators, the preparation of proposals and the availability of relevant information found on the subject in the federal universities surveyed. Organized and systematic for different audiences. For praxis to happen, it is necessary to understand the path taken by women and men, specifically in the academic world in the fight against violence against women.
Keywords: Combate a violência contra mulheres; Gênero; Universidades; Combating violence against women; Genre; Universities; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::POLITICA E PLANEJAMENTO GOVERNAMENTAIS